(3eLehYI CSFdI WHjIs
(3ChdgG (B:s
(3SDGd (B: (3bO PcQ GdTjN aj GdbGfhf MjK jJcde aj GdJaSQI bO jchf Hhd CMeQ jLQi ajg ShGO , ajOd Ydi GdMejGJ GdeRefg GdJj ef GdCNdGW GdZdjXI s
(3BNQgG (B:s
(3LhGH Ydi SDGd ai Cf GdBS Ph bhi eJVGOI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B175 - (3U(B179s
(3GfXQgG eY GdeQTO ddQGRi Qbe(B"730"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B219 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj edj (B(1568) s
Keywords: (3GdWHs